2013
DOI: 10.1021/ie3024388
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Dynamics in Pinus sylvestris Kraft Impregnation: Effect of Deacetylation and Galactoglucomannan Degradation

Abstract: During the impregnation stage of a Kraft cooking, dynamic changes occur in wood properties due to the alkali action. Particularly, its ion transport capacity, the effective capillary cross sectional area (ECCSA), is changed due to chemical reactions and swelling. In this work, the ECCSA in the transverse wood direction has been determined for Pinus sylvestris on the basis of the analogy between capillarity and electrical conductivity. Results show that the behavior of ECCSA can be associated with (a) the degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 8 publications
1
7
1
Order By: Relevance
“…The amount of GGM retained was very small even for the experiments with pretreatment at 80°C. Since primary peeling of GGM starts at about 80°C, 22 while primary peeling of cellulose is only significant at 130°C [23][24] it may be that MM stabilizes some cellulose before peeling but that the glucomannan stabilization by MM is too slow compared to primary peeling of glucomannan. The residual alkali was generally within the acceptable ranges of 4-10 g/L.…”
Section: Task 3: Experimental Kinetic Data Of Real Wood Chips (University Of Maine Prof Adriaan Van Heiningen)mentioning
confidence: 99%
“…The amount of GGM retained was very small even for the experiments with pretreatment at 80°C. Since primary peeling of GGM starts at about 80°C, 22 while primary peeling of cellulose is only significant at 130°C [23][24] it may be that MM stabilizes some cellulose before peeling but that the glucomannan stabilization by MM is too slow compared to primary peeling of glucomannan. The residual alkali was generally within the acceptable ranges of 4-10 g/L.…”
Section: Task 3: Experimental Kinetic Data Of Real Wood Chips (University Of Maine Prof Adriaan Van Heiningen)mentioning
confidence: 99%
“…The hydroxide ions will split off acetyl groups, and deacetylation is one of the main alkali-consuming reactions during kraft cooking. Acetyl groups can form strong hydrogen bonds with carboxyl groups, so deacetylation also increases the paths available for diffusion (Sjöström et al 1965;Zanuttini et al 1998;Inalbon and Zanuttini 2008;Inalbon et al 2009a;Montagna et al 2013). For fibre liberation, it would be desired if the lignin located in the middle lamellae would be specially targeted for degradation reactions and dissolution.…”
Section: Impregnation Of Chipsmentioning
confidence: 99%
“…The specific deacetylation kinetics is used and the model is refined considering: (i) the GGM degradation kinetics according to Pannanen et al (2010) and Montagna et al (2013), and (ii) the ionization of phenolic hydroxyl (OH phen ) groups of lignin. This ionization produces additional alkali consumption and generates extra immobile anionic groups.…”
Section: Refined Modelmentioning
confidence: 99%
“…Nevertheless, ECCSA can be better related to the degrees of reaction. Montagna et al (2013) found the following expression of ECCSA as a function of acetyl (AcG), GGM contents, and temperature for pine wood: …”
Section: Initial Concentration (Mol L -1 ) Speciesmentioning
confidence: 99%